Economic Impacts of Population Growth on Electricity Distribution and Consumption in Basra City for the Period 2020-2024 - Jabbar Saleh Al-Eidani , Assist. Lect . Iman (Basra studies journal, 2026)
Population growth in Basra city has a profound impact on the economic assessment of electricity distribution and consumption. Total electricity consumption increased from 3.87 million megawatt-hours in 2020 to 4.84 million megawatt-hours in 2024, corresponding to a compound annual growth rate (CAGR) of 4.6%. The household share of consumption also rose from 54.3% to 57.9% of the total demand, reflecting changes in consumption patterns. This growth has occurred alongside pronounced spatial disparities among administrative districts and a persistent financial gap between cost and revenue, with an annual deficit ranging from 241 to 267 billion IQD. This study aims to analyze these dynamics from a geographical, economic, and spatial perspective using official data for the period 2020–2024, emphasizing the influence of population distribution on electricity consumption and proposing practical strategies to reduce energy losses and enhance network efficiency.